2021
DOI: 10.3390/su13052867
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Soft Computing for Modeling the Strength Properties of Waste Substitute Green Concrete

Abstract: The waste disposal crisis and development of various types of concrete simulated by the construction industry has encouraged further research to safely utilize the wastes and develop accurate predictive models for estimation of concrete properties. In the present study, sugarcane bagasse ash (SCBA), a by-product from the agricultural industry, was processed and used in the production of green concrete. An advanced variant of machine learning, i.e., multi expression programming (MEP), was then used to develop p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Mohammed et al [ 72 ] have previously proven the efficiency and capacity of several predictive models with small MAE values, specifically ranging between 3 and 11. Shah et al [ 73 ] also proved the accuracy of compressive, flexural, and splitting tensile strength models using MAE and RMSE. In their findings, both MAE and RMSE values were considerably low.…”
Section: Resultsmentioning
confidence: 99%
“…Mohammed et al [ 72 ] have previously proven the efficiency and capacity of several predictive models with small MAE values, specifically ranging between 3 and 11. Shah et al [ 73 ] also proved the accuracy of compressive, flexural, and splitting tensile strength models using MAE and RMSE. In their findings, both MAE and RMSE values were considerably low.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Suba (2009) employed ANN for mechanical properties prediction and compared the result with linear regression, the forecast of the ANN model was pretty close to actual work. MEP was used to estimate the mechanical properties of concrete and provide acceptable results as implemented by Shah et al (2021). The parametric study revealed the accuracy of the MEP model, with a high correlation coe cient (R).…”
Section: Mohammed Et Al (2020amentioning
confidence: 99%
“…Nowadays, soft computing methods are widely used in many areas of science. In the literature, one can see numerous scientific papers that have used soft computing methods in mining [ 28 , 29 , 30 , 31 ] and engineering geology [ 32 , 33 , 34 , 35 , 36 , 37 ]. However, in terms of determining the relationship between natural stone properties, noticing such works is difficult.…”
Section: Introductionmentioning
confidence: 99%